2021
DOI: 10.29303/jku.v9i4.443
|View full text |Cite
|
Sign up to set email alerts
|

Profil Efek Samping Penggunaan Antiretroviral Pada Penderita Hiv/Aids Di Poliklinik VCT Di Kota Mataram Tahun 2019

Abstract: Latar Belakang: Di Indonesia, upaya penanganan infeksi HIV menerapkan pendekatan fast track 90-90-90, dengan satu indikatornya yaitu pemberian ARV pada penderita HIV. ARV lini pertama yang digunakan di Indonesia saat ini yaitu tenofovir, lamivudine/emtricitabine, dan efavirenz dalam bentuk kombinasi dosis tetap (KDT). Namun, penggunaan ARV dapat menimbulkan efek samping dari reaksi ringan hingga berat. Penelitian ini bertujuan untuk mengetahui efek samping yang ditimbulkan ARV pada penderita HIV/AIDS di Polikl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(22 reference statements)
0
0
1
Order By: Relevance
“…We found the 3 most common LTE side effects among people living with HIV in this study, that were headache, nausea, and nightmares. This was slightly different from a study finding in Mataram that LTE side effects among people living with HIV were weakness, dizziness, and vomiting where these side effects were still in the mild category [37], while another study in India found the most common side effect of LTE among people living with HIV was drowsiness, followed by headaches and nightmares [21]. In general, the most common side effects experienced by people living with HIV in this study were symptoms due to central nervous system disorder.…”
Section: Discussioncontrasting
confidence: 95%
“…We found the 3 most common LTE side effects among people living with HIV in this study, that were headache, nausea, and nightmares. This was slightly different from a study finding in Mataram that LTE side effects among people living with HIV were weakness, dizziness, and vomiting where these side effects were still in the mild category [37], while another study in India found the most common side effect of LTE among people living with HIV was drowsiness, followed by headaches and nightmares [21]. In general, the most common side effects experienced by people living with HIV in this study were symptoms due to central nervous system disorder.…”
Section: Discussioncontrasting
confidence: 95%